Hubungan antara Frekuensi Bangkitan Pasien Epilepsi dengan Tingkat Stres Psikososial - Mangnga, Pandu D.; Pertiwi, Junita M.; Mahama, Corry N. (Medical Scope Journal, 2025)
Abstract: Epilepsy is a chronic neurological disorder of the brain characterized by recurrent seizures due to excessive electrical discharge in a group of brain cells. The frequency of seizure that occurs in patients with epilepsy often causes social stigma that has an impact on the psychosocial aspects of the individual. This study aimed to determine the relationship between the frequency of epileptic seizure and psychosocial stress level in patients with epilepsy at the Neurology Polyclinic of Prof. Dr. R. D. Kandou Hospital Manado. This was an analytical and observational study with a cross-sectional design. This study was conducted at the Neurology Polyclinic of Prof. Dr. R. D. Kandou Hospital Manado from October to November 2024. The sampling technique used consecutive sampling with research instruments using the Perceived Stress Scale (PSS-10) questionnaire and patient medical record data. The results obtained 28 patients with epilepsy as samples. The majority of patients experienced moderate levels of psychosocial stress (75%), with the frequency of awakening <1 time per month (46.42%). The Spearman correlation test obtained a p-value of 0.070 indicating that there was no significant relationship between the frequency of epileptic seizures and the level of psychosocial stress. In conclusion, there is no significant relationship between the frequency of epileptic seizures and the level of psychosocial stress among patients with epilepsy. Keywords: patients with epilepsy; seizure frequency; psychosocial stress level Abstrak: Epilepsi merupakan gangguan neurologis kronis pada otak, ditandai dengan bangkitan berulang akibat pelepasan muatan listrik berlebihan pada sekelompok sel otak. Frekuensi bangkitan yang terjadi pada pasien epilepsi sering menyebabkan munculnya stigma sosial yang berdampak pada aspek psikososial dari individu tersebut. Penelitian ini bertujuan untuk mengetahui hubungan antara frekuensi bangkitan pasien epilepsi dengan tingkat stres psikososial di Poliklinik Saraf RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Penelitian ini dilakukan di Poliklinik Saraf RSUP Prof. Dr. R. D. Kandou Manado pada bulan Oktober sampai November 2024. Teknik pengambilan sampel menggunakan consecutive sampling dengan instrumen penelitian menggunakan kuesioner Perceived Stress Scale (PSS-10) dan data rekam medik pasien. Hasil penelitian mendapatkan 28 pasien epilepsi sebagai sampel penelitian. Mayoritas pasien mengalami stres psikososial tingkat sedang (75%), dengan frekuensi bangkitan <1 kali/bulan (46,42%). Hasil uji korelasi Spearman mendapatkan nilai signifikansi p=0,070, yang menunjukkan tidak terdapat hubungan bermakna antara frekuensi bangkitan epilepsi dengan tingkat stres psikososial. Simpulan penelitian ini ialah tidak terdapat hubungan bermakna antara frekuensi bangkitan epilepsi dengan tingkat stres psikososial di Poliklinik Saraf RSUP Prof. Dr. R. D. Kandou Manado. Kata kunci: pasien epilepsi; frekuensi bangkitan; tingkat stres psikososial